Raising the dead : readings of death and (Black) subjectivity - Holland, Sharon Patricia (New Americanists., 2000)
Raising the Dead is a groundbreaking, interdisciplinary exploration of death's relation to subjectivity in twentieth-century American literature and culture. Sharon Patricia Holland contends that black subjectivity in particular is connected intimately to death. For Holland, travelling through "the space of death" gives us, as cultural readers, a nuanced and appropriate metaphor for understanding what is at stake when bodies, discourses, and communities collide. Holland argues that the presence of blacks, Native Americans, women, queers, and other "minorities" in society is, like death, "almost unspeakable." She gives voice to--or raises--the dead through her examination of works such as the movie Menace II Society, Toni Morrison's novel Beloved, Leslie Marmon Silko's Almanac of the Dead, Randall Kenan's A Visitation of Spirits, and the work of the all-white, male, feminist hip-hop band Consolidated. In challenging established methods of literary investigation by putting often-disparate voices in dialogue with each other, Holland forges connections among African-American literature and culture, queer and feminist theory. Raising the Dead will be of interest to students and scholars of American culture, African-American literature, literary theory, gender studies, queer theory, and cultural studies